Profile and Stability of Specific Physical Fitness in Elite Female Football Players Throughout the Season - Carolina Zamith Soares Teixeira (2024)
Women's football has experienced substantial growth in recent decades, both in terms of participation and international recognition. However, significant gaps remain in scientific research regarding the physical and physiological demands specific to elite female players. This study aims to analyze the profile and stability of the physical fitness of professional players in the Liga BPI throughout a competitive season, focusing on key components such as lower limb strength and power, speed, and the ability to perform and sustain intense intermittent exercise with a high rate of aerobic and anaerobic energy turnover. Twelve players were assessed at two points during the season. Tests included standing long jump (SLJ), vertical jump (ABL), 10 and 40-meter sprints, lower limb isokinetic strength, and the Yo-Yo Intermittent Recovery Test - Level 1 (YYIR1). The assessments were conducted during competitive breaks to avoid interference with the team's preparation. The results revealed significant improvements in the players' physical capacities over the season. The SLJ distance increased from 1.90 ± 0.01 m to 1.94 ± 0.02 m (p = 0.014), while ABL height rose from 35.5 ± 4.0 cm to 36.7 ± 3.9 cm (p = 0.011). Sprint times for 10 meters decreased from 2.23 ± 0.02 s to 1.95 ± 0.01 s (p < 0.001), and for 40 meters from 6.08 ± 0.02 s to 5.91 ± 0.02 s (p < 0.001), reflecting an improvement in speed. Lower limb isokinetic strength, particularly in the dominant leg, also increased significantly. However, the ability to perform and sustain intense intermittent exercise with a high rate of aerobic and anaerobic energy turnover, assessed by the YYIR1 test, remained stable, with total distance covered varying from 1011 ± 215 m to 1024 ± 265 m (p = 0.881). These results suggest a good adaptation of the players to the demands of the season, with attention needed to address potential muscular imbalances.